Sonographic imaging of extra-testicular focal lesions: comparison of grey-scale, colour Doppler and contrast-enhanced ultrasound. (February 2016) - Rafailidis, Vasileios; Robbie, Hasti; Konstantatou, Eleni; Huang, Dean Y; Deganello, Annamaria; Sellars, Maria E; Cantisani, Vito; Isidori, Andrea M; Sidhu, Paul S
Extra-testicular lesions are usually benign but present with nonspecific grey-scale sonography findings. This study assesses conventional sonographic characteristics in the differentiation of extra-testicular tumoural from inflammatory lesions and whether contrast-enhanced ultrasound has a role. A retrospective database analysis was performed. All patients were examined by experienced sonographers employing standard techniques combining grey-scale, colour Doppler sonography and contrast-enhanced ultrasound. Features recorded were: clinical symptoms, size, location, echogenicity, colour Doppler sonography and contrast-enhanced ultrasound enhancement. Vascularity on colour Doppler sonography and contrast-enhanced ultrasound was graded and compared. The lesions were classified as tumoural or inflammatory. The Chi-square test was used to analyse the sonographic patterns and kappa coefficient to measure the agreement between colour Doppler sonography and contrast-enhanced ultrasound. A total of 30 lesions were reviewed (median diameter 12 mm, range 5–80 mm, median age 52 years, range 18–86 years), including 13/30 tumoural and 17/30 inflammatory lesions. Lesions were hypoechoic ( n = 12), isoechoic ( n = 6), hyperechoic ( n = 2) or mixed ( n = 10). Grey-scale characteristics of tumoural vs. inflammatory lesions differed significantly ( P = 0.026). On colour Doppler sonography, lesions had no vessels ( n = 16), 2–3 vessels ( n = 10) and ≥4 vessels ( n = 4). On contrast-enhanced ultrasound, lesions showed no vascularity ( n = 17), perfusion similar to testis ( n = 7) and higher ( n = 6). All abscesses identified ( n = 9) showed no vascularity on both colour Doppler sonography and contrast-enhanced ultrasound. There was good agreement between these techniques in evaluating vascularity ( κ = 0.719) and no significant difference between colour Doppler sonography and contrast-enhanced ultrasound of tumoural vs. inflammatory lesions ( P > 0.05). The grey-scale appearances of extra-testicular lesions are essential for characterisation. Colour Doppler sonography and contrast-enhanced ultrasound findings are not useful in that respect. Contrast-enhanced ultrasound is excellent in establishing absence of vascularity.